Is There a Tradeoff between Ethnic Diversity and Redistribution? The Case of Income Assistance in Canada - David A. Green; W. Craig Riddell (Institute of Labor Economics (IZA), 2019)
Numerous studies conclude that ethnic/cultural/racial diversity has negative impacts on interpersonal trust and support for redistributive social programs. Although some Canadian public opinion data is consistent with this view, whether these impacts on public opinion are important enough to influence policy is unclear. Many scholars argue that Canada is an exception to experience elsewhere. This paper examines this question for the case of Canadian social assistance (welfare) policies - a central component of the social safety net. We exploit two salient features of recent Canadian experience. One is dramatic growth in the ethnic and cultural diversity of Canada's immigrant inflows in recent decades, but the extent of this growth has varied substantially across regions. The second is that welfare policies vary across provinces, and the ability of the provinces to employ different approaches to welfare programs has increased since the mid-1990s. We thus examine whether provinces that became more diverse reduced the generosity of their welfare programs, relative to provinces that experienced little change in the heterogeneity of their populations. We examine impacts of immigration on welfare benefit rates of four family types: single employables, single disabled, lone parents and couples with children. Our main finding is that there is limited evidence of increased immigration on any of these types other than families with children. Even in this case the estimated effects are small. Our study thus supports the view that Canada's experience stands as an example in which greater diversity has not reduced support for redistributive social programs.
Keywords: H0; I3; J6; 330; redistribution; social assistance; welfare; immigration; multiculturalism; ethnic diversity; interpersonal trust